2017
DOI: 10.1007/s00018-017-2713-8
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell therapy: is this the end of the beginning?

Abstract: The prevalence of liver diseases is increasing globally. Orthotopic liver transplantation is widely used to treat liver disease upon organ failure. The complexity of this procedure and finite numbers of healthy organ donors have prompted research into alternative therapeutic options to treat liver disease. This includes the transplantation of liver cells to promote regeneration. While successful, the routine supply of good quality human liver cells is limited. Therefore, renewable and scalable sources of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 196 publications
(260 reference statements)
0
40
0
1
Order By: Relevance
“…While donor hepatocytes have been used to successfully treat metabolic liver disease (Alwahsh et al 2018 ), the graft is eventually lost. This is further compounded by the scarcity of human hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…While donor hepatocytes have been used to successfully treat metabolic liver disease (Alwahsh et al 2018 ), the graft is eventually lost. This is further compounded by the scarcity of human hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with inborn liver-based metabolic disorders are good candidates for cell transplantation, presenting only defects in enzymes or transport proteins for which even partial correction will significantly improve a patient's condition. Successful clinical trials have been reported in treating liver-based metabolic disorders in pediatric patients, and numerous studies are currently being carried out in order to improve cell availability and safety as well as medical procedures [32,33]. Nevertheless, all these studies allowed for the identification of some critical parameters for the optimal organ repopulation by transplanted cells and the anticipated clinical outcome.…”
Section: Cell Therapy: Transplantation Of Isolated Cellmentioning
confidence: 99%
“…The ECM plays a crucial role in cellular organization and function. 61 Several approaches have been investigated, including co-culture and the development of 3-dimensional (3D) systems. 62,63 It is possible that cells grown in 3D systems would behave more like cells in vivo and be implanted directly.…”
Section: Tissue Engineeringmentioning
confidence: 99%